A SEMIOTICS STUDY ON METAPHOR USED IN ENGLISH TRANSLATIONOF HADITH BUKHARI - Abdul Azis, Muhammad (2011)
The objectives of this study are (1) to describe the variation symbols of metaphor (2) to identify the meaning of the metaphor symbol in English Translation of Hadith Bukhari. In this study, the writer uses qualitative research as the type of study. To collect the data, the writer uses documentation method. This method is proposed to find out and observe metaphor symbol Expression in English Translation of Hadith Bukhari. The data source of the research is Hadith Bukhari. This research applied semiotics approach as the technique of analyzing data by identifying symbol categories from metaphor. Viewed from semiotic approach, semiotics term (the relation between sign and object) can be divided into three categories: symbol, index, and icon. Symbol /symbolic is a mode in which the signifier does not resemble the signified but which is fundamentally arbitrary of purely conventional and must be learned. While, the correlation between sign and object of icon is resembling or imitating the signified. Then index is cause effect relation between sign and signified. The results of the research show that: (1) the variation of symbol, the variation of symbol is divided into two types: human/man is 62%, abstract/being is 38%. The high percentage of variation of symbol are human symbol (2) the meaning of variation metaphor the use in English translation of Hadith Bukhari have some matters beautifying, reminding, expressing sarcasm, criticizing, threatening and commanding.